Studies on prevalence of biofilm associated genes and primary observation on sasX gene in clinical isolates of coagulase negative staphylococci (CoNS). Issue 4 (4th February 2016) - Soumya, Kandammuriyil Radhakrishnan; Mathew, Shiji; Sugathan, Sheela; Mathew, Jyothis; Radhakrishnan, Edayileveettil Krishnankutty
Abstract : Coagulase negative staphylococci (CoNS) are nosocomial pathogens that cause indwelling medical device associated infections due to its biofilm forming potential and multiple antibiotic resistance. The current study focused on species identification, antibiotic resistance profile and molecular basis of biofilm formation and attachment of CoNS isolated from clinical samples. Along with this, molecular screening for mec A and newly identified surface colonization protein encoded by sas X gene was also conducted. S. epidermidis (n = 19, 47%) was identified as the most prevalent CoNS species and very interestingly two biofilm forming, mec A positive S. epidermidis isolates were found to carry all the biofilm associated genes screened in this study, which indicates its potential to form the strong biofilm. Another novel observation of the study is the detection of sas X gene in one biofilm positive S. epidermidis isolate. The study also identified one doxycycline resistant mec A positive, multidrug resistant S. haemolyticus isolate. In conclusion, the study signifies the existence of multiple biofilm related genes, multidrug resistance and the presence of sas X gene among clinical isolates of CoNS.